2010
DOI: 10.1111/j.1472-4642.2010.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Spreading to a limit: the time required for a neophyte to reach its maximum range

Abstract: Williamson et al. worked with range sizes on a logit scale of grid squares and estimated, using reduced major axis (RMA) analyses, the time for neophytes (alien plants introduced after 1500 ad) to achieve the same average range size as natives. They assumed that all neophytes would eventually reach a maximum range even though none of their data sets showed a clear asymptote and argued that the neophyte average maximum would, in time, match the native average. They found times of 151, 177, 145 and 141 years for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…2), probably for the same reasons. It has been recently shown that it takes on average about 150 years for an alien plant species in Europe to achieve a full distribution according to Williamson et al (2009) and Gassó et al (2010). Those authors also showed that, although many aliens are still in the process of extending their ranges, it may be assumed that some have made more progress than others.…”
Section: Patterns Of Invasion Of Widely Distributed Plant Species Arementioning
confidence: 95%
“…2), probably for the same reasons. It has been recently shown that it takes on average about 150 years for an alien plant species in Europe to achieve a full distribution according to Williamson et al (2009) and Gassó et al (2010). Those authors also showed that, although many aliens are still in the process of extending their ranges, it may be assumed that some have made more progress than others.…”
Section: Patterns Of Invasion Of Widely Distributed Plant Species Arementioning
confidence: 95%
“…Concern is also heightened because many introduced populations remain innocuous for extended periods before spreading and becoming invasive [30,31]. For instance, Brazilian pepper remained restricted in Florida for a century before rapidly expanding across a wide area [30], whereas plants introduced to Europe might take 150-400 years to reach their fullest areal extent [32].…”
mentioning
confidence: 99%
“…The reason for such lags is often mysterious, but their existence cannot be doubted. Further, even introduced species that do not experience a pronounced lag often take a long time to reach their fullest extent; for plants introduced in Europe, this time appears to average 150 years (Gassó et al 2010). Simply by the subtle initial nature of many invasions that ultimately have substantial ecosystem consequences, it is likely that many introduced species whose impact has not yet occurred or been recognized will turn out to have ecosystem impacts.…”
Section: Lag Timesmentioning
confidence: 99%